2016
DOI: 10.1167/iovs.16-19088
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Tear Evaporation Rates After Eyelid Warming Therapies in Meibomian Gland Dysfunction

Abstract: Citation: Yeo S, Tan JH, Acharya UR, Sudarshan VK, Tong L. Longitudinal changes in tear evaporation rates after eyelid warming therapies in meibomian gland dysfunction. Invest Ophthalmol Vis Sci. 2016;57:197457: -198157: . DOI:10.1167 PURPOSE. Lid warming is the major treatment for meibomian gland dysfunction (MGD). The purpose of the study was to determine the longitudinal changes of tear evaporation after lid warming in patients with MGD.METHODS. Ninety patients with MGD were enrolled from a dry eye clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
1
40
0
1
Order By: Relevance
“…Some studies have shown that older age groups (>45 years) have 1.5 times higher evaporation rates than younger adults and women have evaporation rates approximately 1.4 times higher than men [244246], but other studies have failed to show any impact of age or sex [240,247]. Subjects who blink more than normal (likely being a consequence of evaporation) or have a larger exposed ocular surface have increased tear evaporation rates [246,248].…”
Section: Biophysical Measurements Of the Tear Filmmentioning
confidence: 99%
“…Some studies have shown that older age groups (>45 years) have 1.5 times higher evaporation rates than younger adults and women have evaporation rates approximately 1.4 times higher than men [244246], but other studies have failed to show any impact of age or sex [240,247]. Subjects who blink more than normal (likely being a consequence of evaporation) or have a larger exposed ocular surface have increased tear evaporation rates [246,248].…”
Section: Biophysical Measurements Of the Tear Filmmentioning
confidence: 99%
“…The most effective and well-known treatment is warm compress combined with lid massage, which heats the glands and alleviates gland obstruction [2, 3]. However, for this treatment to be effective, an intensive treatment regimen is required to be performed by the patient, making patient compliance low [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, the practitioner has to use several tools to evaluate tear production, tear film stability, ocular surface damage, and other subjective symptoms. Tear evaporation measurements using devices with a closed chamber system, [3][4][5] ventilating chamber system, 6 or infrared thermography 7 have been reported previously. However, direct measurement of TE is not currently feasible in clinical practice.…”
mentioning
confidence: 99%